2007
DOI: 10.1073/pnas.0700901104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the leucine-rich repeat protein LINGO-1 enhances survival, structure, and function of dopaminergic neurons in Parkinson's disease models

Abstract: The nervous system-specific leucine-rich repeat Ig-containing protein LINGO-1 is associated with the Nogo-66 receptor complex and is endowed with a canonical EGF receptor (EGFR)-like tyrosine phosphorylation site. Our studies indicate that LINGO-1 expression is elevated in the substantia nigra of Parkinson's disease (PD) patients compared with age-matched controls and in animal models of PD after neurotoxic lesions. LINGO-1 expression is present in midbrain dopaminergic (DA) neurons in the human and rodent bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
183
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 34 publications
(72 reference statements)
10
183
0
1
Order By: Relevance
“…Previous studies have revealed that many known regulatory roles of Nogo-A rely on Nogo-66-NgR/p75/ LINGO-1-RhoA-ROCK pathway, 2 which are reported to play important roles in several neuronal death models. [17][18][19][20] We then assessed whether these components participated in the neuroprotection. Cell death assay showed no significant difference from that of control with several different signaling blockers, such as 1E8 and 2B3 mAb against Nogo-A, 15 TAT-NEP1-40 (Nogo extracellular peptide, residues 1-40), 20 soluble LINGO-1-Fc 18 and TAT-C3 protein (Figures 4a-d).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that many known regulatory roles of Nogo-A rely on Nogo-66-NgR/p75/ LINGO-1-RhoA-ROCK pathway, 2 which are reported to play important roles in several neuronal death models. [17][18][19][20] We then assessed whether these components participated in the neuroprotection. Cell death assay showed no significant difference from that of control with several different signaling blockers, such as 1E8 and 2B3 mAb against Nogo-A, 15 TAT-NEP1-40 (Nogo extracellular peptide, residues 1-40), 20 soluble LINGO-1-Fc 18 and TAT-C3 protein (Figures 4a-d).…”
Section: Resultsmentioning
confidence: 99%
“…35 Overexpression of LINGO1 is also observed in several neuronal disorders including multiple sclerosis, Parkinson disease, and essential tremor. 36 Various association studies have also shown the role of LINGO1 variants with essential tremor and Parkinson's disease. 37 Moreover, inhibitory anti-LINGO1 antibodies promoted illegitimate oligodendrocyte differentiation and myelination of neurons by inhibiting the function of LINGO1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the binding of LINGO-1 to the EGFR has been shown to directly inhibit EGFR expression. This results in a dampening of PI3K/Akt signaling, which has been shown to protect dopaminergic neurons from apoptosis (12). LINGO-1 has also been shown to associate with TrkB in the regulation of RGC survival (30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, blocking LINGO-1 function improves midbrain dopaminergic neuron survival in an animal model of Parkinson disease (12), increases RGC survival in a rat model of chronic glaucoma (11), and protects cerebellar granule neurons from low potassiuminduced apoptosis (13). Moreover, genetic analysis suggests that the LINGO1 gene may be an attractive target when developing therapies for the treatment of neurodegenerative diseases that are thought to be characterized by neuronal apoptosis (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation